Information needs of coffee producers associated with the Cooperativa Agropecuaria Industrial y de Servicios Múltiples de Atenas, Costa Rica - Hernández Arroyo, Wilson (2024)
The study investigates the information needs of coffee producers in Atenas, Costa Rica, associated with COOPEATENAS R.L. It adopts a naturalistic paradigm with a qualitative descriptive and exploratory approach. Three types of study subjects were selected using non-probabilistic samples, and techniques such as focus groups and semi-structured interviews were employed. Descriptive and narrative analysis helped understand the information needs based on identified labor problems. The results reveal that producers face technical, economic, political, and socio-institutional information needs stemming from daily challenges. These needs are crucial for optimizing production and adapting to regulatory and commercial changes. The study concludes by emphasizing the importance of comprehensively addressing the labor difficulties and informational demands of coffee producers. It recommends establishing effective communication mechanisms and fostering collaboration among entities involved in production.